Awareness Of Swayam Courses Among The Prospective Teachers In Sivaganga District - K.Jeyakumari, Dr.A.Balu (International Journal of Advanced Science and Technology, 2020)
This paper the investigator studied the awareness of swayam course among the prospective teachers. The education behindhand the term is described by its inventors as simple and uncompromising as creating an open and dispersed learning experience. The explanation of SWAYAM is ‘Study Webs of Active Learning for Young Aspiring Minds. The consciousness of MOOCs - SWAYAM among prospective Teachers. MOOCs deliver the irreplaceable opportunity to attach with comprehensive beginners without conservative restraints such as period, currency, and landscape. The investigator established the Survey method for the present study and administered it to the prospective Teachers. The researcher had chosen the Simple Random sampling technique for the study. 200 Prospective Teachers were the sample for this study. The researcher had selected the objective questionnaire form. The tool had 45 items. The MOOCs - SWAYAM Awareness Inventory was prepared and developed by the investigator. The consistency and rationality of the tool were recognized. SWAYAM is a digital stand by which any single can effortlessly record and knowledge at anytime.